Culture and conceptualisations of nature : an interpretive analysis of Australian and Chinese perspectives. - Slay, Jill (Curtin University, 2000)
Issues of culture and worldview and their impact on students' learning of science have become increasingly important to science teachers. This study details work that I carried out in the period 1995-1999 which examined the effect of culture on students' conceptualisations of nature. It is framed as the creation of my own 'living educational theory' as I, a teacher-researcher, dealt with what I perceived were the cultural inequities experienced by students in my classroom. I carried out my first study with a group of seven rural high school students in the Far North of Queensland in Australia, where I was teaching in 1995. Later, in two visits to China, I was able to carry out the same sort of research with a group of seven Chinese college students in Jinan, Shandong Province, PRC, largely using the Chinese language. I used a naturalistic inquiry approach and a semi-structured interview technique to determine students' conceptualisations of nature. I have chosen to embed the results of these two studies within narratives that describe my experiences in the two cultures as I carried out my research. For each culture, I have also developed an epic description of the role of science from the literature and history of that culture. From my three sources of data, interview, narrative and historical description, I have made knowledge claims about the students' beliefs about the natural world.My research findings are ironic to me since they are diametrically opposite to what I had expected. Initially I had believed that Mainland Chinese students would possess a world view full of alternative perspectives to that of Western school science. My research indicates however that students in rural Mainland China hold a traditional and integrated modem Western scientific world view. Although some researchers in other South-East Asian communities propose alternative frameworks for the teaching of science, frameworks that are actually 'pre-modern' these do not appear to be appropriate for Mainland Chinese students. I had expected that the Australian students would bring a modern Western scientific world view to the science classroom. However, the group of rural Western students that I interviewed displayed a world view that is not recognisable as that of modern Western science. Postmodernism and other cultural and social effects appear to have influenced them to such an extent that some have clearly not 'crossed the border' to a modern Western scientific world view. This thesis reflects my desire to overcome the perceived problem of inequity in my own teaching. The knowledge claims made here give some indication as to how I may improve my own practice. A return to the classroom will allow me to continue the cycle of action and reflection by which I can validate, develop and refine my living educational theory.